The finishing space value for shooting decision-making in high-performance football - Caldeira, N.; Lopes, R. J.; Araujo, D.; Fernandes, D. (Sports, 2024)
Football players` decision-making behaviours near the scoring target (finishing situations) emerge from the evolving spatiotemporal information directly perceived in the game`s landscape. In finishing situations, the ball carrier`s decision-making about shooting or passing is not an individual decision-making process, but a collective decision that is guided by players` perceptions of match affordances. To sustain this idea, we collected spatiotemporal information and built a model to quantify the "Finishing Space Value" (FSV) that results from players` perceived affordances about two main questions: (a) is the opponent`s target successfully reachable from a given pitch location?; and (b) from each given pitch location, the opposition context will allow enough space to shoot (low adversaries` interference)? The FSV was calculated with positional data from high-performance football matches, combining information extracted from Voronoi diagrams (VD) with distances and angles to the goal line. FSV was tested using as a reference the opinion of a "panel of expert" (PE), composed by football coaches, about a questionnaire presenting 50 finishing situations. Results showed a strong association between the subjective perception scale used by the PE to assess how probable a shot made by the ball carrier could result in a goal and FSV calculated for that same situation (R^2=0.6706). Moreover, we demonstrate the accuracy of the FSV quantification model in predicting coaches` opinions about what should be the "best option" to finish the play. Overall, results indicated that the FSV is a promising model to capture the affordances of the shooting circumstances for the ball carrier`s decision-making in high-performance football. FSV might be useful for more precise match analysis and informing coaches in the design of representative practice tasks.